EFEKTIFITAS PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ANAK ADHD - Diana Diana (Universitas Negeri Padang, 2012)
The background of this research is based on the ADHD child DII / C class had difficulty in math. Because, children often said they could not receive a lesson in the methods that are tedious. The purpose of this study was to improve the numeracy skills for children with ADHD. Type of this research used is classroom action research is conducted in collaboration with colleagues to investigate the subject II D / C class with two of his students are male sex. Presentation of results and data analysis can be summed up using snakes and ladders game to improve numeracy skills for children with ADHD II D / C class.